Japanese atmospheres of criminal justice - Young, Alison (The British journal of criminology, 2019)
What is a criminal justice atmosphere? Defined as that connecting individuals within and to the spaces they occupy or move through, the study of criminal justice atmospheres can add to thinking within criminology about space, affect and the aesthetic. Examination of criminal justice atmospheres teaches much about how institutions operate as environments choreographing a range of spatial, affective and aesthetic attachments for citizens. Through ethnographic research in Japan, the article considers the atmospheres of three settings: the koban, or ‘police box’, a museum dedicated to the leisure consumption of policing and a metropolitan prison. Reflexive engagement with aspects of Japanese criminal justice can reveal points of congruence through which taken-for-granted understandings of Western criminal justice processes may be questioned, critiqued and enriched. Reading their atmospheres enables our understanding both of their intended modes of operation and the possibilities for their interruption.